PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Saman, Saman; Febriani, Erika; KURNIAWAN, Ase; Anwar, Saeful (Prodi PAI IAILM Suryalaya, 2022)
This study aims to determine the effect of the role of Islamic Religious Education teachers on the character of students in Serba Bakti Islamic Junior High School. The research method used is descriptive with a quantitative approach, namely research in the form of revealing current conditions by considering past conditions through processing the numbers obtained in the study. Based on the results of this study, it can be concluded that the character of students can be built through the role of Islamic Religious Education teachers on the character of students at SMP Islam Serba Bakti. It is recommended for teachers to provide a sense of humor when teaching and involve students in learning, and for students it is recommended to be more active in religious activities and be punctual in doing assignments